2014
DOI: 10.1149/2.0701414jes
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Studies of Resolution in Scanning Ion Conductance Microscopy

Abstract: Spatial resolution of images recorded with scanning ion conductance microscopy (SICM) was examined with well-defined samples prepared by focused-ion beam (FIB) milling. Fiduciary standards of controlled size, shape, and spacing were investigated as a function of imaging parameters and pipette tip size. Topographic images of the standards were acquired in ac feedback mode. We report that two features can be resolved when spaced apart at distances as small as 0.5x the probe inner radius, in agreement with recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 14 publications
2
36
0
Order By: Relevance
“…and 2d) make it clear that with V = 0, the phase shift can be used as a set point for determining topography and being able to position the probe at close tip-to-substrate separations, which is important for enhancing the resolution of SICM. 56,57 In a similar way to the experimental approaches at non-zero bias (Figure 2), the model predicts a dramatic change of the phase-distance behavior for V  0.…”
Section: Resultssupporting
confidence: 63%
“…and 2d) make it clear that with V = 0, the phase shift can be used as a set point for determining topography and being able to position the probe at close tip-to-substrate separations, which is important for enhancing the resolution of SICM. 56,57 In a similar way to the experimental approaches at non-zero bias (Figure 2), the model predicts a dramatic change of the phase-distance behavior for V  0.…”
Section: Resultssupporting
confidence: 63%
“…While there are some limitations of these simulations, in that they assumed nanopipettes to exhibit a conical geometry, the results help to understand the SICM response and various factors such as the nanopipette size required to achieve a desired resolution, and the tip-surface separation distances that would be needed. It should be noted that there is some discrepancy between simulated and experimental studies of resolution in SICM [98], because experiments have suggested that a resolution as small as 0.5r in [98,99] is possible.…”
Section: Modellingmentioning
confidence: 98%
“…105 Initial adoption of this technique was slow but in recent times the popularity of SICM has dramatically increased, particularly for the biological sciences due to the potential to provide contact-free imaging of so, delicate surfaces, such as living cells. [116][117][118][119][120][121] The simplest means of positional feedback is by measuring DC between the pipette and bulk solution electrodes but, more commonly, the tip is modulated via a small, vertical oscillation to give an AC signal. [116][117][118][119][120][121] The simplest means of positional feedback is by measuring DC between the pipette and bulk solution electrodes but, more commonly, the tip is modulated via a small, vertical oscillation to give an AC signal.…”
Section: Ion Conductance Positioningmentioning
confidence: 99%
“…117 Experimentally, the limit of lateral resolution has been independently shown to be 0.5 r i , 110,117 where r i is the inner radius of the pipette, although theoretical studies suggest this should be closer to 2-3 times r i . The exact denition of resolution for SICM varies greatly: Baker and co-workers have recently examined previous experimental and theoretical limits of SICM resolution and highlight these discrepancies.…”
Section: Ion Conductance Positioningmentioning
confidence: 99%
See 1 more Smart Citation